Ultra-light shock-absorbing EVA sole and its preparation process

By adjusting the raw material composition and process flow of the EVA sole, improving the foaming rate and reducing the density of the sole, combined with specific filler composition and modifiers, the shortcomings of existing sports soles in terms of ultra-light and shock absorption effects are solved, and lighter and better shock absorption performance are achieved.

CN116102814BActive Publication Date: 2025-05-02MAOTAI FUJIAN SOLES CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111332357.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-11
Publication Date
2025-05-02
Estimated Expiration
2041-11-11

AI Technical Summary

Technical Problem

The existing sports shoe soles have shortcomings in achieving ultra-light and shock absorption effects, and the production process is complicated and the effect is not obvious.

Method used

By defining the specific raw material composition and addition amount of EVA sole, the foaming rate is increased to 2.2-2.4 times, combined with the combination of maleic anhydride grafted polyethylene wax and hydroxypropyl methacrylate, azodiformamide and fatty acid polyoxyethylene ether sodium sulfate and polyethylene glycol are used as foaming agents, and the composition of the filler is controlled to achieve ultra-light and shock-absorbing properties of the sole.

Benefits of technology

The sole density is less than 0.1g/cm3, the overall weight is light and the shock absorption performance is good, which reduces the overall quality of the sole and improves the shock absorption performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003349263290000041
    Figure BDA0003349263290000041
  • Figure BDA0003349263290000051
    Figure BDA0003349263290000051
  • Figure BDA0003349263290000081
    Figure BDA0003349263290000081
Patent Text Reader

Abstract

An ultralight shock-absorbing EVA sole and a preparation process thereof. The EVA sole is composed of the following raw materials: ethylene-vinyl acetate copolymer, polystyrene-butadiene copolymer, foaming agent, filler, silicone polyether emulsion, maleic anhydride grafted polyethylene wax, dicumyl peroxide, diethylene glycol, zinc stearate, hydroxypropyl methacrylate, triethylenediamine, and propylene glycol. The invention limits the specific raw material composition and addition amount of the EVA sole, increases the foaming rate to 2.2-2.4 times, and makes the density of the prepared EVA sole less than 0.1g / cm 3 , so that the overall weight of the sole is light and the shock absorption performance is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of foaming sole preparation, and in particular relates to an ultra-light shock-absorbing EVA sole and a preparation process thereof. Background Art

[0002] There are various new styles of shoes on the market that can meet certain needs of athletes, but there are not many shoes with good functionality. With the improvement of living standards, fitness exercises are increasingly in demand by the public, and the sole is the most important component of sports shoes. It has the functions of providing shock absorption, stability and flexibility. The existing sports shoe soles are achieved by controlling the formula of foaming materials, the temperature during production and the molding time, etc. The production process is complicated. The soles are used in sports shoes, and the ultra-light and shock-absorbing effects are not obvious. To produce ultra-light, shock-absorbing and practical shoes, not only advanced materials but also advanced technical structures are required. Summary of the invention

[0003] The object of the present invention is to overcome the shortcomings of the prior art and provide an ultra-light shock-absorbing EVA sole. Another object of the present invention is to provide a preparation process of the above-mentioned EAV sole.

[0004] The present invention adopts the following technical solution:

[0005] An ultralight shock-absorbing EVA sole is composed of the following raw materials in parts by weight: 70-80 parts of ethylene-vinyl acetate copolymer, 35.7-42.8 parts of polystyrene butadiene copolymer, 3.3-3.9 parts of foaming agent, 13.6-17.5 parts of filler, 0.8-1.2 parts of silicone polyether emulsion, 18.2-21.5 parts of maleic anhydride grafted polyethylene wax, 1.6-2.1 parts of dicumyl peroxide, 2.7-3.5 parts of diethylene glycol, 2-2.6 parts of zinc stearate, 7.9-9.5 parts of hydroxypropyl methacrylate, 0.3-0.5 parts of triethylenediamine and 0.75-0.9 parts of propylene glycol.

[0006] Furthermore, the foaming agent is composed of azodicarbonamide, sodium polyoxyethylene fatty acid ether sulfate, and polyethylene glycol in a ratio of 1:1.36-1.49:0.72-0.78 by mass.

[0007] Furthermore, the filler is composed of wood powder, glass fiber and mica powder in a mass ratio of 1:1-2:1.5-2.5.

[0008] Furthermore, the foaming ratio of the EVA sole is controlled at 1:2.2-2.4.

[0009] A preparation process of an ultra-light shock-absorbing EVA sole comprises the following steps:

[0010] Step 1, firstly mix the raw materials other than the blowing agent, dicumyl peroxide, hydroxypropyl methacrylate, and maleic anhydride grafted polyethylene wax according to weight parts, and then perform banburying, adjust the temperature to 70-85° C., keep it for 3 minutes, and then turn the material;

[0011] Step 2: When the temperature rises to 90°C, add part of the maleic anhydride grafted polyethylene wax, turn the material over for the second time, and when the banburying temperature rises to 93°C, turn the material over for the third time and add hydroxypropyl methacrylate and maleic anhydride grafted polyethylene wax;

[0012] Step 3: When the mixing temperature rises to 98°C, add dicumyl peroxide and foaming agent for the fourth time, and when the mixing temperature rises to 104°C, turn the material for the fifth time;

[0013] Step 4, when the temperature rises to 110°C, turn the material over for the sixth time, and then mix for 1 minute, pour the material, mix and granulate to obtain EVA pellets;

[0014] Step 5, pouring the granules into the EVA injection machine, and injecting the EVA sole in one time.

[0015] Furthermore, in the step 2, the amount of maleic anhydride grafted polyethylene wax added is 70% of the total amount.

[0016] Furthermore, in step five, the temperature of the injection machine is 170-185° C., the mold temperature is 170-185° C., and the time is 180-210 seconds.

[0017] It can be seen from the above description of the present invention that, compared with the prior art, the present invention has the following beneficial effects:

[0018] First, the present invention increases the foaming rate to 2.2-2.4 times by limiting the specific raw material composition and addition amount of the EVA sole, so that the density of the prepared EVA sole is less than 0.1g / cm 3 , so that the overall weight of the sole is light and the shock absorption performance is good;

[0019] Second, maleic anhydride grafted polyethylene wax is limited to be combined with hydroxypropyl methacrylate as a modifier to make the blend easier to foam, increase the foaming rate to 2.2-2.4 times, shorten the foaming time, and reduce the preparation time of the sole;

[0020] Third, azodicarbonamide, sodium fatty alcohol polyoxyethylene ether sulfate, and polyethylene glycol are limited to be used as foaming agents in combination with dicumyl peroxide, so that the blend forms a uniform closed pore structure, the bubbles are independent of each other, and the bubbles are not connected to each other, which reduces the overall quality of the sole and improves the shock absorption performance of the sole;

[0021] Fourth, by limiting the specific composition of the filler, the shrinkage rate of the sole is reduced and the stability of the sole size after foaming is improved. Among them, maleic anhydride grafted polyethylene wax can be combined with the filler to improve and enhance the compatibility and adhesion of the filler to the substrate interface, thereby greatly improving the shock absorption performance of the sole. DETAILED DESCRIPTION

[0022] The present invention is further described below through specific implementation modes.

[0023] An ultralight shock-absorbing EVA sole is composed of the following raw materials in parts by weight: 70-80 parts of ethylene-vinyl acetate copolymer, 35.7-42.8 parts of polystyrene butadiene copolymer, 3.3-3.9 parts of foaming agent, 13.6-17.5 parts of filler, 0.8-1.2 parts of silicone polyether emulsion, 18.2-21.5 parts of maleic anhydride grafted polyethylene wax, 1.6-2.1 parts of dicumyl peroxide, 2.7-3.5 parts of diethylene glycol, 2-2.6 parts of zinc stearate, 7.9-9.5 parts of hydroxypropyl methacrylate, 0.3-0.5 parts of triethylenediamine and 0.75-0.9 parts of propylene glycol.

[0024] The foaming agent is composed of azodicarbonamide, sodium polyoxyethylene fatty acid ether sulfate and polyethylene glycol in a mass ratio of 1:1.36-1.49:0.72-0.78.

[0025] The filler is composed of wood powder, glass fiber and mica powder in a mass ratio of 1:1-2:1.5-2.5.

[0026] The foaming ratio of EVA sole is controlled at 1:2.2-2.4.

[0027] A preparation process of an ultra-light shock-absorbing EVA sole comprises the following steps:

[0028] Step 1, firstly mix the raw materials other than the blowing agent, dicumyl peroxide, hydroxypropyl methacrylate, and maleic anhydride grafted polyethylene wax according to weight parts, and then perform banburying, adjust the temperature to 70-85° C., keep it for 3 minutes, and then turn the material;

[0029] Step 2, when the temperature rises to 90°C, add maleic anhydride grafted polyethylene wax according to 70% of the weight of maleic anhydride grafted polyethylene wax, turn the material for the second time, when the banburying temperature rises to 93°C, turn the material for the third time and add hydroxypropyl methacrylate and maleic anhydride grafted polyethylene wax;

[0030] Step 3: When the mixing temperature rises to 98°C, add dicumyl peroxide and foaming agent for the fourth time, and when the mixing temperature rises to 104°C, turn the material for the fifth time;

[0031] Step 4, when the temperature rises to 110°C, turn the material over for the sixth time, and then mix for 1 minute, pour the material, mix and granulate to obtain EVA pellets;

[0032] Step 5, pouring the granules into an EVA injection machine, and injecting the EVA sole once, wherein the temperature of the injection machine is 170-185° C., the mold temperature is 170-185° C., and the time is 180-210s.

[0033] Example

[0034] Each embodiment and comparative example was prepared with reference to the parameters in Table 1 (unit: g)

[0035]

[0036]

[0037] Example 1

[0038] An ultralight shock-absorbing EVA sole, whose raw material composition is shown in Table 1, wherein the foaming agent is composed of azodicarbonamide, sodium polyoxyethylene fatty acid ether sulfate, and polyethylene glycol in a ratio of 1:1.36:0.78 by weight; and the filler is composed of wood powder, glass fiber, and mica powder in a ratio of 1:1:1.5 by weight.

[0039] The preparation process comprises the following steps:

[0040] Step 1, firstly mix the raw materials other than the blowing agent, dicumyl peroxide, hydroxypropyl methacrylate, and maleic anhydride grafted polyethylene wax according to weight parts, and then perform banburying, adjust the temperature to 70° C., keep it for 3 minutes, and then turn the material over;

[0041] Step 2, when the temperature rises to 90°C, add maleic anhydride grafted polyethylene wax according to 70% of the weight of maleic anhydride grafted polyethylene wax, turn the material for the second time, when the banburying temperature rises to 93°C, turn the material for the third time and add hydroxypropyl methacrylate and maleic anhydride grafted polyethylene wax;

[0042] Step 3: When the mixing temperature rises to 98°C, add dicumyl peroxide and foaming agent for the fourth time, and when the mixing temperature rises to 104°C, turn the material for the fifth time;

[0043] Step 4, when the temperature rises to 110°C, turn the material over for the sixth time, and then mix for 1 minute, pour the material, mix and granulate to obtain EVA pellets;

[0044] Step 5, pouring the granules into an EVA injection machine, and injecting the EVA sole in one shot, wherein the temperature of the injection machine is 185° C., the mold temperature is 185° C., and the time is 180 seconds.

[0045] Example 2

[0046] An ultralight shock-absorbing EVA sole, whose raw material composition is shown in Table 1, wherein the foaming agent is composed of azodicarbonamide, sodium polyoxyethylene fatty acid ether sulfate, and polyethylene glycol in a ratio of 1:1.49:0.72 in parts by mass; and the filler is composed of wood powder, glass fiber, and mica powder in a ratio of 1:2:2.5 in parts by mass.

[0047] The preparation process comprises the following steps:

[0048] Step 1, firstly mix the raw materials except the blowing agent, dicumyl peroxide, hydroxypropyl methacrylate, and maleic anhydride grafted polyethylene wax according to weight parts, and then perform banburying, adjust the temperature to 85° C., keep it for 3 minutes, and then turn the material;

[0049] Step 2, when the temperature rises to 90°C, add maleic anhydride grafted polyethylene wax according to 70% of the weight of maleic anhydride grafted polyethylene wax, turn the material for the second time, when the banburying temperature rises to 93°C, turn the material for the third time and add hydroxypropyl methacrylate and maleic anhydride grafted polyethylene wax;

[0050] Step 3: When the mixing temperature rises to 98°C, add dicumyl peroxide and foaming agent for the fourth time, and when the mixing temperature rises to 104°C, turn the material for the fifth time;

[0051] Step 4, when the temperature rises to 110°C, turn the material over for the sixth time, and then mix for 1 minute, pour the material, mix and granulate to obtain EVA pellets;

[0052] Step 5, pouring the pellets into an EVA injection machine, and injecting the EVA sole in one shot, wherein the temperature of the injection machine is 170° C., the mold temperature is 170° C., and the time is 210 s.

[0053] Example 3

[0054] An ultralight shock-absorbing EVA sole, whose raw material composition is shown in Table 1, wherein the foaming agent is composed of azodicarbonamide, sodium polyoxyethylene fatty acid ether sulfate, and polyethylene glycol in a ratio of 1:1.42:0.75 in parts by mass; and the filler is composed of wood powder, glass fiber, and mica powder in a ratio of 1:1.5:2 in parts by mass.

[0055] The preparation process comprises the following steps:

[0056] Step 1, firstly mix the raw materials other than the blowing agent, dicumyl peroxide, hydroxypropyl methacrylate, and maleic anhydride grafted polyethylene wax according to weight parts, and then perform banburying, adjust the temperature to 78° C., keep it for 3 minutes, and then turn the material over;

[0057] Step 2, when the temperature rises to 90°C, add maleic anhydride grafted polyethylene wax according to 70% of the weight of maleic anhydride grafted polyethylene wax, turn the material for the second time, when the banburying temperature rises to 93°C, turn the material for the third time and add hydroxypropyl methacrylate and maleic anhydride grafted polyethylene wax;

[0058] Step 3: When the mixing temperature rises to 98°C, add dicumyl peroxide and foaming agent for the fourth time, and when the mixing temperature rises to 104°C, turn the material for the fifth time;

[0059] Step 4, when the temperature rises to 110°C, turn the material over for the sixth time, and then mix for 1 minute, pour the material, mix and granulate to obtain EVA pellets;

[0060] Step 5, pouring the pellets into an EVA injection machine, and injecting the EVA sole in one shot, wherein the temperature of the injection machine is 178° C., the mold temperature is 178° C., and the time is 195 seconds.

[0061] Comparative Example 1

[0062] The raw material composition and preparation method are basically the same as those of Example 3, except that the foaming agent is azodicarbonamide.

[0063] Comparative Example 2

[0064] The raw material composition and preparation method thereof are substantially the same as those of Example 3, with the difference being that the foaming agent is composed of azodicarbonamide and sodium polyoxyethylene fatty acid ether sulfate in a mass ratio of 1:1.42.

[0065] Comparative Example 3

[0066] The raw material composition and preparation method thereof are substantially the same as those of Example 3, except that the foaming agent is composed of azodicarbonamide and polyethylene glycol in a ratio of 1:0.75 by mass.

[0067] Comparative Example 4

[0068] The raw material composition and preparation method thereof are substantially the same as those of Example 3, except that maleic anhydride grafted polyethylene wax is not added to the raw material composition; and in step three, only hydroxypropyl methacrylate is added during the third turning of the material.

[0069] Comparative Example 5

[0070] The raw material composition and preparation method thereof are substantially the same as those of Example 3, except that hydroxypropyl methacrylate is added to the raw material composition; and in step three, only maleic anhydride grafted polyethylene wax is added during the third turning of the material.

[0071] Comparative Example 6

[0072] The raw material composition and preparation method are basically the same as those of Example 3, except that the filler is talcum powder.

[0073] The foamed soles prepared in the above-mentioned embodiments and comparative examples were subjected to corresponding tests to obtain the following data, as shown in Table 2.

[0074] Among them, the impact rebound rate test uses the GT-7042-RE impact elasticity testing machine;

[0075] Compression deformation test refers to HG / T2876 (temperature 50°C, time 6 hours, compression ratio 50%);

[0076] Dimensional shrinkage is tested in accordance with ISO 20873:2001.

[0077] Table 2 Performance parameters of each example

[0078]

[0079]

[0080] It can be seen from Table 1 and Table 2 that the present invention increases the foaming rate to 2.2-2.4 times by limiting the specific raw material composition and addition amount of the EVA sole, so that the density of the prepared EVA sole is less than 0.1g / cm 3 , so that the overall weight of the sole is light and the shock absorption performance is good.

[0081] With reference to Example 3 and Comparative Examples 1-3, it can be seen that the EVA sole prepared by the present invention has a lower impact rebound rate, indicating that the prepared EVA sole has good shock absorbing performance. By limiting azodicarbonamide and sodium polyoxyethylene fatty alcohol ether sulfate and polyethylene glycol as foaming agents and cooperating with diisopropylbenzene peroxide, the blend forms a uniform closed pore structure, the bubbles are independent of each other, and the bubbles are not connected to each other, thereby reducing the overall quality of the sole and improving the shock absorbing performance of the sole.

[0082] Referring to Example 3 and Comparative Examples 4-5, it can be seen that limiting the combination of maleic anhydride grafted polyethylene wax and hydroxypropyl methacrylate as a modifier makes the blend easier to foam, increases the foaming rate to 2.2-2.4 times, shortens the foaming time, and reduces the preparation time of the sole.

[0083] With reference to Example 3 and Comparative Example 6, it can be seen that the specific composition of the filler is limited to reduce the shrinkage rate of the sole and improve the stability of the sole size after foaming. Among them, maleic anhydride grafted polyethylene wax can be combined with the filler to improve and enhance the compatibility and adhesion of the filler to the substrate interface, thereby greatly improving the shock absorption performance of the sole.

[0084] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of implementation of the present invention. That is, equivalent changes and modifications made according to the scope of the patent application of the present invention and the contents of the specification should still fall within the scope covered by the patent of the present invention.

Claims

1. An ultra-light shock-absorbing EVA sole, characterized in that: The invention is composed of the following raw materials in parts by weight: 70-80 parts of ethylene-vinyl acetate copolymer, 35.7-42.8 parts of polystyrene butadiene copolymer, 3.3-3.9 parts of foaming agent, 13.6-17.5 parts of filler, 0.8-1.2 parts of silicone polyether emulsion, 18.2-21.5 parts of maleic anhydride grafted polyethylene wax, 1.6-2.1 parts of dicumyl peroxide, 2.7-3.5 parts of diethylene glycol, 2-2.6 parts of zinc stearate, 7.9-9.5 parts of hydroxypropyl methacrylate, 0.3-0.5 parts of triethylene diamine and 0.75-0.9 parts of propylene glycol. The preparation process comprises the following steps: Step 1, firstly mix the raw materials other than the blowing agent, dicumyl peroxide, hydroxypropyl methacrylate, and maleic anhydride grafted polyethylene wax according to weight parts, and then perform banburying, adjust the temperature to 70-85° C., keep it for 3 minutes, and then turn the material; Step 2: When the temperature rises to 90°C, add part of the maleic anhydride grafted polyethylene wax, turn the material over for the second time, and when the banburying temperature rises to 93°C, turn the material over for the third time and add hydroxypropyl methacrylate and maleic anhydride grafted polyethylene wax; Step 3: When the mixing temperature rises to 98°C, add dicumyl peroxide and foaming agent for the fourth time, and when the mixing temperature rises to 104°C, turn the material for the fifth time; Step 4, when the temperature rises to 110°C, turn the material over for the sixth time, and then mix for 1 minute, pour the material, mix and granulate to obtain EVA pellets; Step 5, pouring the pellets into an EVA injection machine, and injecting the EVA sole once; The foaming agent is composed of azodicarbonamide, sodium polyoxyethylene fatty acid ether sulfate, and polyethylene glycol in a mass ratio of 1:1.36-1.49:0.72-0.78; The filler is composed of wood powder, glass fiber and mica powder in a mass ratio of 1:1-2:1.5-2.5; The foaming ratio of the EVA sole is controlled at 1:2.2-2.

4.

2. The ultra-light shock-absorbing EVA sole according to claim 1, characterized in that: In the step 2, the amount of maleic anhydride grafted polyethylene wax added is 70% of the total amount.

3. The ultra-light shock-absorbing EVA sole according to claim 1, characterized in that: In step 5, the temperature of the injection machine is 170-185° C., the mold temperature is 170-185° C., and the time is 180-210 seconds.

Citation Information

Patent Citations

  • Heat-resistant shrinking rubber-plastic blending foaming midsole and formula thereof

    CN108892853A

  • Styrene-butadiene rubber based NANO composite foaming material with high shrinkage stability and preparation method therefor

    WO2018086249A1